SITE SELECTION FOR REGIONAL SOLID WASTE FINAL DISPOSAL IN BANGKA ISLAND BASED ON GEOGRAPHY INFORMATION SYSTEM (GIS) - Sekar Rachmawati Parawangsa; Rahel Situmorang; Benny Suharto (Jurusan Arsitektur - FTSP - Universitas Trisakti, 2020)
The availability of an adequate final disposal a necessity for an area. The waste processing process consists of the stages of transportation, management, final disposal to waste utilization. Waste management in urban areas requires a final disposal that must meet environmental feasibility standards. Problems encountered in the current waste management at the capital city of Bangka Belitung Province, final disposal Parit 6 was already overloaded and still uses the Open Dumping method, and there are limitations in the availability of urban land. The purpose of this study was to selection for the regional solid waste final disposal (RSWFD) in accordance with the characteristics of the local location and the directions in the Spatial Plans of the Province of Bangka Belitung. The method used is a quantitative analysis method by calculating the need for the land area of the waste landfill based on population projections and waste generation. And the model used by the Geography Information System (GIS) in the form of ArcGIS 10.5 is overlaid using parameters based on (SNI 03- 3241-1994). The final result of the research is a recommendation for a RSWFD location for Bangka Island in accordance with the needs, feasibility and availability of existing land.